Revisiting the Period Change and Frequency Analysis of a Variable Star SZ Lyncis - Rattanamala, Ronnakrit; Artsang, Pornapa; Channok, Chanruangrit; Chonsungnoen, Thaweechai; Krinsungnoen, Nutchanat; Ngiabking, Pimmada; Phumnok, Phiyada (Asian Health, Science and Technology Reports, 2024)
This study aims to investigate the period change of the variable star SZ Lyncis. The observations were conducted at the Regional Observatory for the Public, Nakhon Ratchasima (ROP-NMA), operated by the National Astronomical Research Institute of Thailand (NARIT), on January 8th-9th and February 19th-20th 2024. The data was acquired using the CCD camera with a B-filter mount on the 0.7-m reflecting telescope. We report the period change of 1.37(±0.08)´10-12 day cycle-1. Analysis of the O-C diagram revealed the presence of a binary companion with a semi-amplitude of 0.0052(±0.0002) days, the projected semi-major axis of 0.90(±0.04) AU, the eccentricity of 0.25(±0.09), and the orbital period of 1184.1(±1.5) days and the mass function of 0.07(±0.01) M⨀. We also identified the time-series light curve data using the Discrete Fourier transform (DFT) in the Period04 package and obtained results of four frequencies. The main frequency of 8.29630(±0.00002) cycle day-1 corresponds to a period of 0.1205357(±0.0000003) days. These results contribute to our understanding of the pulsation properties of SZ Lyncis and its binary system.